SINTESA MONO-DIGLISERIDA MELALUI REAKSI GLISEROLISIS ENZIMATIS - Eka Kurniasih (Politeknik Negeri Lhokseumawe, 2014)
Mono-Diglycerides are compounds which had properties as a lowering the surface tension. These characteristics of mono-diglycerides are widely used as an emulsifier in food and cosmetic industries. Mono-diglycerides can be synthesized through enzymatic reactions using triglycerides, which contained in many fats and oil. One of potential raw material used as raw material of mono-diglycerides is coconut oil which contains fatty acids C6-C18. The synthesis of mono-diglycerides are generally done through chemical reactions involving solid catalyst at high temperature, thus affecting to the resulting product. To solve this problem, in this research, synthesis of mono-diglycerides done by glyserolisis enzymatic reaction using papain enzyme to replace chemical catalysts. The the research showed that the increasing concentration of papain enzyme did not give a significant influence on the percentage reduction in free fatty acids. But in the papain enzyme concentration of 5% (w/w) and at mole ratio of coconut oil:glycerol (1:10) it obtained the highest product conversion. From the gas chromatografi analysis, it is known that triglyceride had been converted as much as 62.7691% into mono-diglycerides